2017
DOI: 10.1159/000481890
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Transmembrane Protein IQGAP3 Is Associated with Poor Survival of Patients with Gastric Cancer

Abstract: Objective: Spheroid colony formation is a useful method of cancer stem cell (CSC) characterization. We previously showed that the IQ motif containing the GTPase-activating protein 3 gene (IQGAP3) is upregulated in spheroid body-forming gastric cancer (GC) cells compared with parental cells. We investigated IQGAP3 expression in GC. Methods: IQGAP3 protein expression was analyzed by immunohistochemistry in 165 GC cases. RNA interference was used to inhibit IQGAP3 expression in GC cell lines. Results: In non neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
(42 reference statements)
3
23
0
Order By: Relevance
“…As a member of B7 family, B7-H4 may provide negative signals to inhibit or reduce immune response [18]. So far no studies have been found demonstrating the relationship between IQGAP3 and CRC, our findings may verify the role of IQGAP3 played in tumorigenesis and tumor progression [40], and can further clarify the prognostic value of IQGAP3 in CRC patients.…”
Section: Discussionsupporting
confidence: 54%
“…As a member of B7 family, B7-H4 may provide negative signals to inhibit or reduce immune response [18]. So far no studies have been found demonstrating the relationship between IQGAP3 and CRC, our findings may verify the role of IQGAP3 played in tumorigenesis and tumor progression [40], and can further clarify the prognostic value of IQGAP3 in CRC patients.…”
Section: Discussionsupporting
confidence: 54%
“…We previously analyzed the gene expression profile of spheroid colonies and parental cells derived from gastric cancer (GC) cell lines by microarray analysis [10]. We identified several genes upregulated in spheroid colonies, such as KIF11, KIFC1, and IQGAP3, that are required for spheroid colony formation in GC cell lines and are associated with poor survival of GC patients [10][11][12]. These genes are also required for spheroid colony formation in esophageal and colorectal cancer cells [13,14].…”
Section: Tdo2 Overexpression Is Associated With Cancer Stem Cells Andmentioning
confidence: 99%
“…Overexpression of IQGAP3 has been observed in lung, liver, pancreatic and gastric cancer[8-11]. Recently, IQGAP3 expression was found to be related to clinical stage and was an independent prognostic classifier of gastric cancer patients: IQGAP3 knockdown reduced both the number and size of the spheres formed by the gastric cancer cell line MKN-74 and inhibited the phosphorylation of Akt and Erk1/2[11].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of IQGAP3 has been observed in lung, liver, pancreatic and gastric cancer[8-11]. Recently, IQGAP3 expression was found to be related to clinical stage and was an independent prognostic classifier of gastric cancer patients: IQGAP3 knockdown reduced both the number and size of the spheres formed by the gastric cancer cell line MKN-74 and inhibited the phosphorylation of Akt and Erk1/2[11]. In hepatocellular carcinoma, IQGAP3 was reported to function as an important regulator of epithelial-mesenchymal transition (EMT) and metastasis by activating the transforming growth factor (TGF)-β signaling pathway[9].…”
Section: Introductionmentioning
confidence: 99%